ANALYSIS OF SCIENTIFIC RESEARCHES IN PHARMACEUTICAL PROMOTION GLOBALLY: TOWARDS INTERNATIONALLY DEVELOPING PRACTICALLY-ORIENTED GUIDELINES FOR PHARMACEUTICAL COMPANIES - M. M. Bahlol; T. P. Lagutkina (Бюллетень сибирской медицины)
Purpose. Pharmaceutical industry is transnational and globally important. Many pharmaceutical companies operate their business in multinational and international forms in different countries. Diverse researches from different countries indicated and confirmed marketing promotion importance in pharmaceutical field. Therefore, marketing promotion and its effects are a very important issue that should be globally investigated in real life and evidence context. We oriented our research according to these scientific and practical values.Methodology. We reviewed pharmaceutical marketing promotion researches from more than 25 different countries, e.g., USA, Canada, Italy, France, Russia, India, Egypt and Syria where we employed our knowledge of three widely spread languages, i.e., English, Russian and Arabic. Such language variation supports us with large and variable amount of scientific knowledge, deep understanding and ability of analysis. Some studies investigated average response to pharmaceutical marketing promotion and few studies took into consideration heterogeneity in their effects with respect to advertising medium or drug characteristics.Originality. We investigated empirical evidences of pharmaceutical marketing promotion that can be directed to either consumer or healthcare professionals.Findings. We extracted, gathered and associated information of pharmaceutical promotion globally which oriented us to several evidence and practical facts with regard to employing promotion tools in different definite situations pertinent to main directions; their welfare and health enhancing effects and adverse effects. Practical Implications- Consequently, we developed practically-oriented guidelines for companies concerning pharmaceutical promotion globally ate the end of this paper.